Pendidikan Karakter Jujur dalam Pembelajaran Matematika Jarak Jauh di SMPN 26 Kerinci: Tantangan dan Solusinya - Laswadi Laswadi (Departement of Mathematics Education, 2021)
The Covid-19 pandemic has caused distance learning in Indonesia to not be optimal, with challenges for teachers, students and parents in terms of the effectiveness of online learning and the formation of student character. Student honesty in distance learning is an important concern for building integrity and good relationships with teachers and classmates. This study aims to evaluate the process of distance learning at SMPN 26 Kerinci, especially in the formation of students' honest character in mathematics. A qualitative case study approach was used, with data collection techniques in the form of observation and interviews. The results of observations of remote mathematics learning via Zoom show indications that it is necessary to increase the application of honest character of students, with some students turning off the camera, using substitute images, and cheating. Obstacles faced include teacher difficulties in ensuring student attention, lack of social interaction between students and teachers, and the impact felt by parents. Thus, more intensive efforts are needed to form the honest character of students in distance learning.